(untitled) (Papeles, 2019)
In this article we present the consequences of introducing the advanced teaching of the DSGE (Dynamic Stochastic General Equilibrium) models to undergraduate economics programs. This monoculture leads to the deepening of the discipline insularity, to the disappearance of the paradigmatic plurality inside the economics departments and to the silencing of critical voices. This process obeys Gresham’s Law of ideas: bad models displace good ideas.